An Institute for Philippine indigenous music - Cahigas, Jason N. (Manila : National University, 1999)
Indigenous music goes along with dances and it is identified to ritual practices, traditional customs and attributed to certain beliefs of animism.
Title page -- Approval sheet -- Acknowledgement -- Dedication -- Table of contents -- Chapter I. Introduction -- Chapter II. Terms of references -- Chapter III. Research methodology -- Chapter IV. Design framework -- Chapter V. Analysis -- Chapter VI. Summary and Conclusion -- Bibliography -- Annexes.
Includes bibliographical references.
Keywords: INSTITUTE -- PLANNING; INDIGENOUS PEOPLE